Inertial wearables as pragmatic tools in dementia. (September 2019) - Godfrey, A.; Brodie, M.; van Schooten, K.S.; Nouredanesh, M.; Stuart, S.; Robinson, L.
Highlights: Dementia is an important issue with an ever greater impact on society. Wearable devices are now widely discussed as useful pragmatic tools in neurodegenerative diseases. Inertial wearables can quantify postural control and gait to provide useful digital biomarkers in dementia. Lack of standards and lack of access to large data sets are limiting the use of wearables in modern medicine. Abstract: Dementia is a critically important issue due to its wide impact on health services as well as its personal and societal costs. Limitations exist for current dementia protocols, and there are calls to introduce modern technology that facilitates the addition of digital biomarkers to routine clinical practice. Wearable technology (wearables) are nearly ubiquitous in everyday life, gathering discrete and continuous digital data on habitual activities, but their utility in modern medicine remains low. Due to advances in data analytics, wearables are now commonly discussed as pragmatic tools to aid the diagnosis and treatment of a range of neurological disorders. Inertial sensor-based wearables are one such technology; they offer a low-cost approach to quantify routine movements that are fundamental to normal activities of daily living, most notably postural control and gait. Here, we provide a narrative review of how wearables are providing useful postural control and gait data to facilitate the capture of digital markers to aid dementia research. We outline the history of wearables, from their humble beginnings to their current use beyond the clinic, and explore their integration into modern systems, as well as the ongoing standardisation and regulatory efforts to integrate their use in clinical trials.